Development of Attitude Control System on RCM3400 microcontroller for Nano-satellite applications - Muhyi, Yaakop; Sazali, Yaacob; Abdul Rahman, Mohd Saad; Harihran, M.; Nagarajan, R. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.